English Teaching: Bibliometric Analysis of Artificial Intelligence and English Teaching - Alfilail, Nur; Elthia, Memy Wardani; Miswaty, Titik Ceriyani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The phenomenon of Artificial Intelligence nowadays has spread over the world, especially in education. The involvement of Artificial Intelligence in English teaching is essential to study because it shows the trend of how English is taught with the development of AI. The aim of this study is to uncover the trend of Artificial Intelligence and English teaching from 2013 to 2022. This study applied quantitative descriptive method. To find the trend of Artificial Intelligence and English teaching, the data were gathered from Publish or Perish application (PoP) and then visualized by using Vosviewer. To process the data, bibliometric analysis was applied. The data of the study indicates there were 791 publications concerning artificial intelligence and English teaching from 2013 to 2022. Furthermore, the data from 2013 to 2022 related to Artificial Intelligence and English teaching indicates that the number of studies concerning these keywords were gradually increasing from year to year where the year “2021” became the year where the highest number of studies related to Artificial Intelligence were published. Bibliometric analysis in this study showed that the publications concerning Artificial Intelligence and English teaching from 2013 to 2022 were increasing year by year. This finding implies that people now are familiar with applications of technology such as AI in English teaching. Thus, this study can give visualization to other researchers about AI and English teaching. The researcher can explore more detail about the use of Artificial Intelligence in teaching, especially in English teaching.